Development and characterization of antifungal niosomal gel of luliconazole: In vitro and ex vivo approaches - Vibhavari M. Chatur; Shashikant N. Dhole; Nilesh S. Kulkarni; Mithun Rudrapal (Chemical Physics Impact)
Niosomes are multilamellar vesicles that efficiently transfer active substances to epidermal layers or circulation. They improve “active drug skin penetration in topical drug delivery systems. The goal of this work was to develop a luliconazole (LCZ) niosomal gel to promote skin permeability. Luliconazole treats tinea pedis, cruris, and corporis caused by Epidermophyton floccosum and Trichophyton rubrum. Luliconazole has improved skin pharmacokinetics. In the all formulations, the cholesterol ratio was consistent and was prepared by ether injection method using span 60 or tween 80 surfactants. The niosome's entrapment efficiency, size, PDI, and zeta potential were measured. The LSP II formulation with span 60 had the highest noisome entrapment effectiveness (EE), hence carbopol gel was used into it. Niosomal gel pH, spredability, extrudability, practical yield, drug content, in vitro drug release, ex vivo permeability, and biological parameter antifungal activity were measured. The niosomal gel had good homogeneity, spredability, and extrudability at pH 6.5 to 7.4. Out of 4 formulations, F2 had the highest drug concentration (89.70±1.065 %). In vitro drug release investigations used pH 7.4 phosphate buffer. In vitro drug release was highest in formulation F2 (92.09±2.69 %) after 24 h of testing. Franz diffusion cell ex vivo permeation studies of formulation F4 showed excellent drug penetration and flux via animal skin. The cup plate technique showed that formulation F2 had better antifungal efficacy than commercialized formulation against Candida albicans strain.”